Performance of a new type of solar air collector with transparent-vacuum glass tube based on micro-heat pipe arrays. (15th June 2019) - Wang, Teng-yue; Zhao, Yao-hua; Diao, Yan-hua; Ren, Ru-yang; Wang, Ze-yu
Abstract: In this study, a novel solar air collector with transparent-vacuum glass tube is designed and investigated through experiment and numerical simulation. The collector consists of micro-heat pipe arrays (MHPA), selective absorption film and transparent-vacuum glass tube. The absorption film is directly pasted on the MHPA by using heat-conducting glue, which is then placed into transparent-vacuum glass tube. The efficient heat conduction of MHPA and good thermal insulation of the transparent-vacuum glass tube contribute to the high efficiency and low pressure loss of the collector. The collector average efficiency can reach 82.7% and the pressure loss is less than 20 Pa. This collector form for heating spaces and drying crops is new and effective. Increasing the air volume flow rate can considerably improve the collecting efficiency. The ambient temperature in winter results in a higher efficiency than that in summer. Furthermore, a calculation numerical model, which is used to develop 20 collecting units, is established and verified for validity. This model can obtain temperature increase in each collecting unit. Considering the temperature increase in each collecting unit and the thermal efficiency, the proposed maximum collecting unit quantity is 20. Study results provide a theoretical guidance for designing MHPA solar air collector. Highlights: A novel solar air collector based on micro-heat pipe arrays is proposed. The solar air heater has the high efficiency and low pressure loss. A calculation numerical model is established and verified for validity. The numerical calculation provide a theoretical guidance for designing collector.